Reimagining Equality : A New Deal for Children of Color - Dowd, Nancy E., 1949- (Book collections on Project MUSE., 2018)
2018 Outstanding Academic Title, given by Choice MagazineA comprehensive examination of developmental inequality among children Developmental equality-whether every child has an equal opportunity to reach their fullest potential-is essential for children's future growth and access to opportunity. In the United States, however, children of color are disproportionately affected by poverty, poor educational outcomes, and structural discrimination, limiting their potential. In Reimagining Equality, Nancy E. Dowd sets out to examine the roots of these inequalities by tracing the life course of black boys from birth to age 18 in an effort to create an affirmative system of rights and support for all children. Drawing on interdisciplinary research, the book demonstrates that black boys encounter challenges and barriers that funnel them toward failure rather than developmental success. Their example exposes a broader reality of hierarchies among children, linked to government policies, practices, structures, and institutions. Dowd argues for a new legal model of developmental equality, grounded in the real challenges that children face on the basis of race, gender, and class. Concluding with a "New Deal" for all children, Reimagining Equality provides a comprehensive set of policies that enables our political and legal systems to dismantle what harms and discriminates children, and maximize their development.